2019
DOI: 10.1016/j.bbamcr.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Novel CaM-binding motif in its NudT9H domain contributes to temperature sensitivity of TRPM2

Abstract: TRPM2 is a non-selective, Ca 2+ -permeable cation channel, which plays a role in cell death but also contributes to diverse immune cell functions. In addition, TRPM2 contributes to the control of body temperature and is involved in perception of non-noxious heat and thermotaxis. TRPM2 is regulated by many factors including Ca 2+ , ADPR, 2′-deoxy-ADPR, Ca 2+ -CaM, and temperature. However, the molecular basis for the temperature sensitivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The hs TRPM2 structures, together with the structures of TRPM2 in other species, have broadened our understanding of this functionally important channel and allow us to make new hypotheses for how TRPM2 is gated by other factors. For example, the opening of TRPM2 is also regulated by PIP2, temperature, and calmodulin . We speculate that these factors may also modulate the opening of TRPM2 via conformational changes that are similar to what we have observed during the channel opening by ADPR and Ca 2+ .…”
Section: Concluding Remarks and Future Perspectivessupporting
confidence: 77%
“…The hs TRPM2 structures, together with the structures of TRPM2 in other species, have broadened our understanding of this functionally important channel and allow us to make new hypotheses for how TRPM2 is gated by other factors. For example, the opening of TRPM2 is also regulated by PIP2, temperature, and calmodulin . We speculate that these factors may also modulate the opening of TRPM2 via conformational changes that are similar to what we have observed during the channel opening by ADPR and Ca 2+ .…”
Section: Concluding Remarks and Future Perspectivessupporting
confidence: 77%
“…The TRPM2 channel belongs to the superfamily of transient receptor potential (TRP) channels and is a tetrameric Ca 2+ ‐permeable non‐selective cation channel that is gated by intracellular ADP‐ribose (ADPR) and cyclic ADPR . Intracellular Ca 2+ can bind to and activate the TRPM2 channels, and warm temperature (≥35°C) can also induce the TRPM2 channel opening independently of, and more often in synergy with, ADPR or cyclic ADPR . The TRPM2 channel can be potently activated after exposure to pathologically relevant concentrations of ROS, which is thought to stimulate ADPR generation via poly(ADPR) polymerase (PARP), particularly PARP‐1, and poly(ADRP) glycohydrolase (PARG) in the nucleus, and also via NADase in the mitochondria .…”
Section: Trpm2 Channel As a Common Molecular Mechanism Mediating Ros‐mentioning
confidence: 99%
“…[19][20][21][22][23][24][25] Intracellular Ca 2+ can bind to and activate the TRPM2 channels, 26 and warm temperature (≥35°C) can also induce the TRPM2 channel opening independently of, and more often in synergy with, ADPR or cyclic ADPR. 27,28 The TRPM2 channel can be potently activated after exposure to pathologically relevant concentrations of ROS, which is thought to stimulate ADPR generation via poly(ADPR) polymerase (PARP), particularly PARP-1, and poly(ADRP) glycohydrolase (PARG) in the nucleus, and also via NADase in the mitochondria. 15 The TRPM2 channel is expressed in many different types of cells, 15 and a large body of evidence has been accumulated, since two seminal studies reported at the beginning of this century, 29,30 that supports the TRPM2 channel as an important and widespread molecular mechanism conferring the susceptibility to cell death induced by ROS and also by a diversity of pathological factors that are known to induce ROS generation.…”
Section: Trpmchannel a S A Common Molecul Ar Mechanis M Mediating Rmentioning
confidence: 99%
“…Due to the fact that Ca 2+ represents a cofactor for channel activation of TRPM2, a potential regulatory role for calmodulin has also been suggested. For hTRPM2 there is some experimental evidence for this idea, both at the sequence level and in functional respect [36,74]. Further studies in particular cryo-EM-analyses are necessary to clarify this issue.…”
Section: Open Questions and Future Strategiesmentioning
confidence: 98%
“…In this context, apparently a specific sequence of NUDT9H which is missing in drTRPM2 plays a crucial role [68]. In hTRPM2 this so-called P-loop located within the N-terminal part of NUDT9H [68] was identified as a putative binding site for calmodulin and was associated with temperature-dependent channel activation [74].…”
Section: Nudt9h-species-specific Functional Characteristics and Evolumentioning
confidence: 99%